Interest Rate Smoothing and Time-Varying Premium: Another Look at Debt Management in Japan - Yosuke Takeda (Yale University, Economic Growth Center, 1999)
We argue a source of time-varying premium (TVTP) in Japanese government bond market, and show that it is interest rate smoothing that causes empirical failures of expectation theory of term structure of interest rates. We estimate a regime switching ARCH model where an interest rate smoothing regime can be identified. Based on a model of time-inconsistency by Missale and Blanchard (1994), we further focus on a role of debt maturity in TVTP, which is an alternative to an ARCH process. Our robust empirical evidences support the expectation theory in Japanese government bond market. Moreover, in comparison with the ARCH process, debt maturity turns out to be a reliable proxy for the TVTP. This shows a possibility of a debt management policy in Japan: fiscal authority takes advantage of the debt maturity for price stability which is a target of monetary policy. It sharply contrasts with an evidence for ineffectiveness of the U.S. debt management policy by Wallace and Warner (1996).
Keywords: E42; E43; E52; 330; Time-Varying Term Premium; Interest Rate Smoothing; Regime Switching ARCH Model; Debt Maturity; Reputation Equilibrium; Staatspapier; Zinspolitik; Schuldenmanagement; Inflationsbekämpfung; Zinsstruktur; ARCH-Modell; Schätzung; Japan